Організація моделі управління групою користувачів соціальної мережі в глобальному інформаційному середовищі - Білик, Василь; Форкун, Юрій (Видавництво Львівської політехніки, 2016)
Based on learning functions of users groups in social networks is carried problem statement for model management of group. Also are listed main factors and components ensuring effective management of users group. Represented components for model management of group.
Keywords: група в соціальній мережі; управління групою; модель управління; ефективність управління